Biogenic synthesis of silver nanoparticle by Cytobacillus firmus isolated from the river sediment with potential antimicrobial properties against Edwardsiella tarda - Kumar, Vikash; Parida, Satya Narayan; Dhar, Souvik; Bisai, Kampan; Sarkar, Dhruba Jyoti; Panda, Soumya Prasad; Das, Basanta Kumar (Frontiers in Microbiology, 2024)
The aquatic environment, independent of their host, is more favorable to pathogenic bacteria than the terrestrial environment. Consequently, pathogenic bacteria can reach very high densities around aquatic animals and can cause high mortality. The conventional approach, such as antibiotics, has minimal effectiveness. Additionally, due to the emergence of (multiple) resistance, their use is under intense scientific and public scrutiny. Hence, there is a need for the development of alternative control techniques, with an emphasis on prevention, which is likely to be more cost-effective. In this study, a potential bacterial strain Cytobacillus firmus was isolated from polluted river sediment and characterized using a comprehensive range of techniques including biochemical, 16S rRNA sequencing and antibiogram assay. The pathogenicity of the bacteria was tested in vivo on Labeo rohita fingerlings found as non-pathogenic. Further, the bacteria were found to synthesize silver nanoparticles (AgNPs) using AgNO3 as a substrate. The obtained AgNPs were characterized by various methods, including UV–vis spectroscopy, FTIR (Fourier-transform infrared spectroscopy), and Transmission Emission Microscopy (TEM). The study found that the AgNPs were 20 nm in size on average. The antimicrobial activity of synthesized AgNPs was examined against the model freshwater pathogenic bacteria, Edwardsiella tarda and both the MIC (Minimum Inhibitory Concentration) and MBC (Minimum Bactericidal Concentration) were 0.156 μM, while biofilm inhibition activity was also observed at 0.156 μM. The AgNPs showed no haemolytic activity at 0.313 μM. Our findings suggest that C. firmus mediated bacteriogenic AgNPs modulate the activity of common pathogenic bacteria E. tarda. The thoroughness of our research process gives us confidence in the potential of applying AgNPs in aquaculture as a considerable strategy to control the E. tarda infection.